2022
DOI: 10.3390/app12031491
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Aware Multi-Objective Job Shop Scheduling Optimization with Metaheuristics in Manufacturing Industries: A Critical Survey, Results, and Perspectives

Abstract: In recent years, the application of artificial intelligence has been revolutionizing the manufacturing industry, becoming one of the key pillars of what has been called Industry 4.0. In this context, we focus on the job shop scheduling problem (JSP), which aims at productions orders to be carried out, but considering the reduction of energy consumption as a key objective to fulfill. Finding the best combination of machines and jobs to be performed is not a trivial problem and becomes even more involved when se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…Since seven of these papers are reviews, we ended up with 172 papers to be further synthesized, analyzed, and reported on. This is almost four times the number of JSP and FJSP papers reviewed in the most recently published literature reviews [2][3][4]. Moreover, of these 172 papers, 115 have been published since 2019.…”
Section: Review Scope and Methodologymentioning
confidence: 92%
See 2 more Smart Citations
“…Since seven of these papers are reviews, we ended up with 172 papers to be further synthesized, analyzed, and reported on. This is almost four times the number of JSP and FJSP papers reviewed in the most recently published literature reviews [2][3][4]. Moreover, of these 172 papers, 115 have been published since 2019.…”
Section: Review Scope and Methodologymentioning
confidence: 92%
“…The search was conducted on the two most well-established bibliographic databases: Web of Science™ and Scopus ® . To avoid missing relevant papers due to varying authors' keyword choices, papers were also gathered through backward/forward reference search, including from the most recent review papers [2][3][4][5].…”
Section: Review Scope and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although energy efficiency in manufacturing systems can be addressed in many ways, such as adopting renewable resources, using improved machinery, and redesigning products and production processes, researchers have proved energy-efficient scheduling to be an effective way of reducing energy consumption. Additionally, scheduling optimization is easier to apply to existing systems and requires far less capital investment, if at all, making it more widely applicable; especially for small and medium enterprises (Fernandes, Homayouni, and Fontes 2022;Para, Del Ser, and Nebro 2022;Gahm et al 2016).Two solution methods were developed to solve the proposed EEJSPT-MS: a bi-objective mixed-integer linear programming model (MILP), and a multi-objective multi-population biased random key genetic algorithm (mpBRKGA). MILP's can provide exact optimal solutions but are usually too computationally demanding and slow to solve large instances in a reasonable timeframe, and thus are deemed unsuitable for real-world applications for this problem.…”
mentioning
confidence: 99%
“…Although energy efficiency in manufacturing systems can be addressed in many ways, such as adopting renewable resources, using improved machinery, and redesigning products and production processes, researchers have proved energy-efficient scheduling to be an effective way of reducing energy consumption. Additionally, scheduling optimization is easier to apply to existing systems and requires far less capital investment, if at all, making it more widely applicable; especially for small and medium enterprises (Fernandes, Homayouni, and Fontes 2022;Para, Del Ser, and Nebro 2022;Gahm et al 2016).…”
mentioning
confidence: 99%